Normative Examination of the Mandatory Public Housing Savings Scheme for Self-Employed Workers in Relation to Consumer Protection and the Constitution - Zulham; Noor Azizah (Journal of Indonesian Legal Studies, 2026)
The Public Housing Savings Law (UU Tapera) requires self-employed workers earning at least the minimum wage to participate as Tapera members, even though their income is not connected to any employer. This obligation stands in contrast to the Consumer Protection Law (UUPK), which ensures that consumers have the right to freely select goods and/or services based on their individual preferences. As Tapera consumers, self-employed workers should therefore retain the freedom to determine the financing model and capital-accumulation scheme they prefer for obtaining residential housing. Additionally, the 1945 Constitution of the Republic of Indonesia (UUD 1945) guarantees every individual’s right to adequate housing. This article examines the compatibility of Article 7 paragraph (1) of the Public Housing Savings Law with Article 4 letter (b) of the Consumer Protection Law and Article 28H paragraph (1) of the 1945 Constitution. Using a normative juridical research method, the study analyzes primary, secondary, and tertiary legal materials on Tapera for self-employed workers from the perspectives of consumer protection and constitutional law. These materials are assessed to formulate scholarly insights presented in a constructive and argumentative manner. The study concludes that Article 7 paragraph (1) of the Public Housing Savings Law is inconsistent with the Consumer Protection Law and the constitutional guarantee of adequate housing. Accordingly, the article recommends clearly distinguishing the terms “workers” and “self-employed workers” in the law and regulating Tapera participation for self-employed workers on a voluntary basis.